Design and cyclic testing of bolted end plate connections between steel link beams and cross-laminated timber for coupled shear walls. (24th October 2022) - Moerman, Ben; Li, Minghao; Smith, Tobias; Lim, Hyungsuk
Highlights: Popular bolted end plate connection has been adapted for coupled CLT wall systems. Bolted end plates can provide high-capacity timber connections in a coupled timber wall. A simple analytical model conservatively predicts the connection strength. Capacity design of the connection for a 200UB18 link beam was successful. Abstract: Coupled cross-laminated timber (CLT) wall systems with ductile steel link beams offer an efficient, high-capacity lateral load resisting system for buildings in earthquake-prone regions. This study proposes a type of beam to CLT wall connection using a bolted end plate in a notched CLT panel edge to create a semi-rigid joint. A simplified analytical method is proposed to predict the connection strength and is compared against the results of full-scale experiments. The experimental strength values were all greater than the predictions from the proposed method. Therefore, the strength method seems conservative and is suitable for the capacity design of similar connections in coupled wall systems. The final specimen in the test programme was capacity designed and its cyclic test results demonstrated adequate connection strength and relatively high stiffness were achieved for a 200 mm-deep wide flange link beam. The specimen's link beam yielded at an applied shear load of 180kN and reached a maximum strength of 278kN while dissipating a large amount of energy through steel yielding. The bolted end plate connection appears to be a practical solution for application in coupled CLT shear walls.